I've tried putting it up as:

$$ [u_1 v_1 + \ldots + u_n v_n] = [u_1 w_1 + \ldots + u_n w_n] $$

But this doesn't make it immediately clear...I can't simply divide by $u_1 + \ldots + u_n$ as these ($u$, $v$ and $w$) are vectors...

Any hints?

  • 9
    $\begingroup$ There must be more to this. Perhaps it's supposed to say that if, for every vector $u$ one has $u\cdot v = u\cdot w$, then $v=w$? As it is, the statement is simply false. $\endgroup$
    – MJD
    May 14 '14 at 15:31
  • 3
    $\begingroup$ (As an example of what MJD's talking about) $(1,0,0)\cdot(0,1,0)=0$ and $(1,0,0)\cdot(0,0,1)=0$ but but $(0,1,0)\neq(0,0,1)$. Is the question you really want to ask the on MJD mentions? $\endgroup$
    – rschwieb
    May 14 '14 at 15:31
  • $\begingroup$ What if $u=0$?! $\endgroup$ May 14 '14 at 15:36
  • $\begingroup$ It just says: Suppose we know that $u v = u w$, does it follow that $v = w$? So I guess I could say: ''No, if u=0, then this does not need to hold''? $\endgroup$ May 14 '14 at 16:04
  • $\begingroup$ . . . or you could give examples where $u\ne0$. $\endgroup$ May 14 '14 at 16:54

If $u\cdot v=u\cdot w$ for all $u$ (equivalently $u\cdot(v-w)=0$), then with $u=v-w$, we get $\|v-w\|^2=(v-w)\cdot(v-w)=0$. Hence $v=w$.

P.S.: Of course, if $v$ are $w$ assumed to be vectors from some inner-product space $S$ with a basis $s_1,\ldots,s_k$, then "for all $u$" can be replaced by "for $u=s_i$, $i=1,\ldots,k$".

  • $\begingroup$ Hah, that's even better :) $\endgroup$
    – rschwieb
    May 14 '14 at 15:37
  • $\begingroup$ I'd never seen this one before; gorgeous! $\endgroup$ May 14 '14 at 15:41
  • $\begingroup$ But what does $u=s_i=v-w$ mean then? $\endgroup$
    – mavavilj
    Feb 26 '18 at 7:43

Presumably you want to add "for all $u$" to that question.

Rearranging, you get $u\cdot (v-w)=0$.

If $v-w\neq 0$, can you see how to pick a $u$ so that $u\cdot(v-w)\neq 0$? A very simple choice of $u$ would work.

By contrapositive, you will have proved that if $u\cdot (v-w)=0$ for all $u$, then $v=w$.


$$ u\cdot v=u\cdot w $$

Others have shown how to show that $v=w$ if one assumes the above for all values of $u$.

To show that it's now true if one just assumes $u$, $v$, $w$ are some vectors, let's look at the circumstances in which it would fail. Recall that $u\cdot v = \|u\| \|v\|\cos\theta$ where $\theta$ is the angle between the vectors $u$ and $v$.

Thus one circumstance in which the conclusion does not hold is when $v$ and $w$ are of equal lengths, i.e. $\|v\|=\|w\|$, and both are at the same angle with $u$. Just draw a picture. One can rotate $v$ about an axis in which the vector $u$ lies and get many vectors $w$ having the same length as $v$ and making the same angles with $u$.

Another circumstance in which it fails is this: picture $u$ and $v$ as arrow pointing out from the origin, and draw a plane or hyperplane at right angles to $u$ passing through the endpoint of the arrowhead of $v$. Choose an arbitrary point in that hyperplane, and draw an arrow from the origin to that point. Call that vector $w$. Then show that $u\cdot v=u\cdot w$.


Can I not choose $u=(1,0,0)$, $u=(0,1,0)$ and $u=(0,0,1)$. When I plug them into $u\cdot v=u\cdot w$, I get three equations: $v_1=w_1$, $v_2=w_2$ and $v_3=w_3$, so $v$ must be equal to $w$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.